The Effect of Sulfentrazone and Glyphosate Herbicides to Control Eleusine Indica L. a Resistant weed to Herbicide - Cam Hong Ha; Ardi Ardi; Indra Dwipa (Department of Crop Science, Faculty of Agriculture, Andalas University, 2022)
Weed Eleusine indica L. was reported to have been difficult to control using glyphosate in Oil palm plantation during the time. Sulfentrazone was used as an alternative herbicide for the management of resistant weeds. The aim of this study was to determine the effects of two active ingredients Glyphosate and Sulfentrazone on weed Eleusine indica L. resistant to herbicide. The study was conducted using Completely Randomly Designed (CRD) with 14 treatments and 3 replications. 14 treatments consisted of single herbicide Glyphosate, which was applied at field rate 2 l/ha, Sulfentrazone was sprayed at the numerous dose of 500, 750, 1000, and 1250 ml/ha, and the mixture of Glyphosate and sulfentrazone at the dose of 500 ml/ha + 2 l/ha and 750 ml/ha + 2 l/ha, respectively. The research was conducted at the Greenhouse of the Faculty of Agriculture, Andalas University, Padang, from August to December, 2021. The results showed that there were significantly effect when used in combination of herbicides Glyphosate and Sulfentrazone, showed 100% of mortality weed after 3 week application. For a single active ingredient, Glyphosate controlled eficiently weed at the 4-leaf stage, Sulfentrazone had same impact on managing weed on the 4 and 6-leaf stage, both caused 100% weed dead. However, weed Eleusine indica L. was treated with Glyphosate still survived on 6 and 8 leaves weeds. Similar to Glyphosate, Sulfentrazone could not completely control resistant weeds at the 8-leaf stage. Classification of resistant weed Eleusine indica L. are herbicide-developing resistance 14%, herbicide-resistant 22%, and herbicide-susceptible 64%.